Financial disclosure and market transparency with costly information processing - Marco Di Maggio; Marco Pagano (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We study a model where some investors ("hedgers") are bad at information processing, while others ("speculators") have superior information-processing ability and trade purely to exploit it. The disclosure of financial information induces a trade externality: if speculators refrain from trading, hedgers do the same, depressing the asset price. Market transparency reinforces this mechanism, by making speculators' trades more visible to hedgers. As a consequence, issuers will oppose both the disclosure of fundamentals and trading transparency. Issuers may either under- or over-provide information compared to the socially efficient level if speculators have more bargaining power than hedgers, while they never under-provide it otherwise. When hedgers have low financial literacy, forbidding their access to the market may be socially efficient.
urn:nbn:de:hebis:30:3-353087
Keywords: D83; D84; G18; G38; K22; M48; 330; disclosure; transparency; financial literacy; limited attention; OTC markets